Application of Nanoemulsion Technology for Preparation and Evaluation of Intranasal Mucoadhesive Nano- In-situ Gel for Ondansetron Hcl - Nidhal K. Maraie (Journal of Global Pharma Technology, 2018)
Objective: Developing more effective and promising in situ gel nasal preparation for ondansetron HCl (OND-HCl) using nanoemulsion (NE) technology and study all the parameters that can optimize the final formula. Method: Screening of oils, surfactants and co-surfactants was performed on the basis of OND-HCl solubility and NE area of emulsifier ratio (Smix), respectively. Pseudo-ternary phase diagrams were constructed by aqueous titration method. Twelve NE formulas were prepared by ultrasonic emulsification and characterized for droplet size, zeta potential, polydispersity index, separation, conductivity, TEM, % transmittance, dilution and visual transparency. The best NE formulation was selected and applied to prepare nano-in situ gel (NIG) using poloxamer 407 as thermoreversible polymer, chitosan and HPMC E15 as mucoadhesive polymers.  The six NIG formulas were evaluated for pH, drug content, osmolarity, gelation temperature, mucoadhesive force, viscosity and in vitro drug release.  Results: The mean droplet size, polydispersity index, zeta potential, conductivity and % transmittance for the selected NE formula (F11) were found to be 64.87 nm, 0.544, - 0.146, 210 μS/cm, and 99.08% respectively. The gelation temperatures, pH, drug content, osmolarity and mucoadhesive force for the selected  NIG formula (NIG6) were 33 ºC, 5.8, 99.215%, 106.06 mOsmol/l (0.62%), 7372.21 dyne/cm² respectively. The in vitro drug release study of NIG6 showed 100% after 6h.  Conclusion: The results of this work indicated the possibility of application of NE technology in the formulation of NIG that has good mucoadhesive force to prolong the preparation residence time in the nose.Keywords: Chitosan, Nano-in situ gel, HPMCE15, Nanoemulsion, Ondansetron HCl.